2013
DOI: 10.1371/journal.pone.0060621
|View full text |Cite
|
Sign up to set email alerts
|

Humans Have Antibodies against a Plant Virus: Evidence from Tobacco Mosaic Virus

Abstract: Tobacco mosaic virus (TMV), a widespread plant pathogen, is found in tobacco (including cigarettes and smokeless tobacco) as well as in many other plants. Plant viruses do not replicate or cause infection in humans or other mammals. This study was done to determine whether exposure to tobacco products induces an immune response to TMV in humans. Using a sandwich ELISA assay, we detected serum anti-TMV antibodies (IgG, IgG1, IgG3, IgG4, IgA, and IgM) in all subjects enrolled in the study (20 healthy smokers, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 48 publications
2
68
0
1
Order By: Relevance
“…In addition, a recent study suggested prevalence of anti-tobacco mosaic virus (TMV) antibodies in humans. [36] Therefore, we set out to determine the IgG titers after repeat administration of various PVX-based formulations and to test whether produced antibodies would recognize the stealth PVX-PEG filaments.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a recent study suggested prevalence of anti-tobacco mosaic virus (TMV) antibodies in humans. [36] Therefore, we set out to determine the IgG titers after repeat administration of various PVX-based formulations and to test whether produced antibodies would recognize the stealth PVX-PEG filaments.…”
Section: Resultsmentioning
confidence: 99%
“…Stealth coatings with polymers have been shown to reduce antibody recognition and clearance of (virus-based) nanoparticles [29]. Both PEG and anti-TMV antibodies have been detected in human subjects, likely due to their presence in cosmetics (PEG) [2], and food chain as well as tobacco products (TMV) [38]. Therefore it is critical to assess whether PEG or POx coatings are efficient to overcome antibody recognition.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it should be noted that plant viruses are in the food chain. On one hand this is a potentially positive attribute, because our bodies have already experienced plant viruses, on the other hand, prevalence of anti-TMV antibodies in healthy volunteers has been reported [38]. Therefore, to improve bioavailability the next-generation of viral nanoparticles must include stealth surface treatments to avoid immune clearance.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important characteristic, given most of the human population has been exposed to TMV through food and tobacco, and have pre-existing anti-TMV IgG titers. 47 Conjugation method also has a significant impact on the quality of the immune response. Glutaraldehyde, which uses random vinyl addition to crosslink proteins, was effective in linking HA to TMV, and stimulated robust single dose titers.…”
Section: Discussionmentioning
confidence: 99%